Immunization with desmoglein 3 induces non-pathogenic autoantibodies in mice - Katharina Boch (Public Library of Science (PLoS), 2021)
Background Pemphigus vulgaris (PV) is a rare autoimmune blistering disease characterized by the development of autoantibodies targeting desmoglein (Dsg) 3, but also against Dsg1 in mucocutaneous disease. Given that existing PV animal models only recapitulate aspects of the disease, we aimed to establish a more comprehensive disease model based on the immunization of mice with PV autoantigen(s). Methods The following immunization strategies were tested: (i) C57Bl/6J, B6.SJL-H2s C3c/1CyJ, DBA2/J, or SJL/J mice were immunized with recombinant murine Dsg3 (mDsg3), (ii) DBA2/J and SJL/J mice were immunized with mDsg3 and additionally injected a single non-blister inducing dose of exfoliative toxin A (ETA), and (iii) DBA2/J and SJL/J mice were immunized with human Dsg (hDsg) 1 and 3. Results Despite the induction of autoantibodies in each immunization protocol, the mice did not develop a clinical phenotype. Tissue-bound autoantibodies were not detected in the skin or mucosa. Circulating autoantibodies did not bind to the native antigen in indirect immunofluorescence microscopy using monkey esophagus as a substrate. Conclusion Immunization with PV autoantigens induced non-pathogenic Dsg1/3 antibodies, but did not cause skin/mucous membrane disease in mice. These findings, confirmed by failure of binding of the induced autoantibodies to their target in the skin, suggest that the autoantibodies which were formed were unable to bind to the conformational epitope present in vivo.